4x+9-6x+11=3(x+5)

Simple and best practice solution for 4x+9-6x+11=3(x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+9-6x+11=3(x+5) equation:


Simplifying
4x + 9 + -6x + 11 = 3(x + 5)

Reorder the terms:
9 + 11 + 4x + -6x = 3(x + 5)

Combine like terms: 9 + 11 = 20
20 + 4x + -6x = 3(x + 5)

Combine like terms: 4x + -6x = -2x
20 + -2x = 3(x + 5)

Reorder the terms:
20 + -2x = 3(5 + x)
20 + -2x = (5 * 3 + x * 3)
20 + -2x = (15 + 3x)

Solving
20 + -2x = 15 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
20 + -2x + -3x = 15 + 3x + -3x

Combine like terms: -2x + -3x = -5x
20 + -5x = 15 + 3x + -3x

Combine like terms: 3x + -3x = 0
20 + -5x = 15 + 0
20 + -5x = 15

Add '-20' to each side of the equation.
20 + -20 + -5x = 15 + -20

Combine like terms: 20 + -20 = 0
0 + -5x = 15 + -20
-5x = 15 + -20

Combine like terms: 15 + -20 = -5
-5x = -5

Divide each side by '-5'.
x = 1

Simplifying
x = 1

See similar equations:

| 7b-7(11-2b)=10 | | p=12+4x | | p=10+2l | | 1/31/2 | | 6x(x+5)=16 | | 6+8a=50+6a-9a | | 12-5u=43 | | p=2l+10 | | x+3x+4x=24 | | 2m+3m-17m=80-m | | 3-3/8X=1/4X | | 1/4(28x-8) | | x+8a=50+ax-9a | | 26/39 | | 1/4X+1/5X=9 | | -3(x+2)=16-2 | | 5-2(x-5)=4x-6 | | 2(2t-5)=20-t | | -28+15-27z=31 | | 1/8y^-5 | | x+8a=50ax-9a | | 5/6X=3-11/12X | | p=x+1+4+4+2+2+x+2+1 | | 6x-3=5x-10x+8 | | 0.7(x+200)=0.75x-225 | | 3(a-2)=6a-(3a+6) | | .2-2=8 | | 3x^2+17x+4=0 | | 5x=5x-3+x-9 | | X/7-X/14+9=X+9 | | 8x+39=2x+15 | | (2/x-3)=(-5/x+5)+(9/(x-3)(x+5)) |

Equations solver categories